A proposito dell’assassinio di Carlo e Nello Rosselli: (9 giugno 1937) - Rosselli, Alessandro (Études sur la Région Méditerranéenne, 2023)
In 2007, in one of his books, the Italian historian Mimmo Franzinelli have connected the assassination of the brothers Carlo and Nello Rosselli at Bagnoles-sur-l’Orne (France), on 9 June 1937, executed by some members of the Cagoule (a French fascist monarchist movement) and ordered by Benito Mussolini, with an article written by Carlo Rosselli and published in the weekly Giustizia e Libertà (Justice and Freedom) on the Italian soldiers take prisoners by the Spanish republican army in the battle of Guadalajara (8-18 March 1937) during the Spanish civil war. In this article, Carlo Rosselli unmasks the lies of the fascist propaganda who have told that all the Italian soldiers in Spain was volunteers when in reality they were all mercenaries. On this connection, Mimmo Framzinelli have reason, and the present article contents an analysis of the text written by Carlo Roselli and some considerations on the injustice on the Rosselli brothers’s killing committed by the Italian justice.